Efficacy of Sothanasaka Sunthyadi Yoga a classical ayurvedic formulation on hemato-biochemical profiles in lactating Holstein Friesian crossbred cows - SURBHI JAIN; MILINDMITRA KASHINATH LONARE; SALONI SINGLA; MANJINDER SHARMA; SIMARJEET KAUR; SANTOSH MANE; SUDESH GAIDHANI; N SRIKANTH; K S DHIMAN (Indian Journal of Animal Sciences)
The current investigation aimed to assess the safety profile of a polyherbal formulation Sothanasaka Sunthyadi Yoga on lactating Holstein Friesian crossbred cattle. A total of 30 animals were selected and divided into three groups. Group 1 received a regular diet (control). Group 2 was administered with Domperidone (10mg/100 kg body weight, orally, positive control) and group 3 was fed with the polyherbal formulation (20 gm/100kg body weight, orally, test group) for the period of 45 days. The effect was evaluated through hematological and biochemical alterations. No change in body weight were observed in all groups. However, there were significant alterations in lymphocyte and neutrophil values noted in groups 2 and 3 on day 60 compared to 0 day. The hemoglobin (Hb) concentration increased significantly from day 0 to day 60 in group 3. The glucose level in group 3 increased significantly on days 30 and 60 when compared with groups 1 and 3 as well as from day 0. Albumin levels increased substantially in all groups, with a significant decrease in total protein in group 2 on day 30 and globulin on day 60. Group 2 showed a significant increase in ALT, AST, ALP and LDH activity when compared with groups 1 and 3. In group 3, LDL and values decreased significantly on day 60, and HDL values decreased significantly on day 30 as compared to group 1. HDL levels in group 2 decreased significantly on day 30. Inflammatory markers, IFN-γ exhibited a significant change in group 3 compared to group 1 with no changes in TNF-α and IL-1β levels. All other parameters remain within a normal limit in the polyherbal-treated groups. In conclusion, the study found that polyherbal preparation Sothanasaka Sunthyadi Yoga treatment did not adversely affect the haemato-biochemical profile, indicating its safety for use in lactating cattle as a galactagogue.